The Economics of Language Policy 2016
DOI: 10.7551/mitpress/9780262034708.003.0012
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Integration and Export Variety Overlap across Countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…While our focus on the interaction between immigrants and common language skills at the country‐pair level is novel (to the best of our knowledge), we draw on several strands of literature. First, irrespective of migrant stocks, many studies have found that a common language increases bilateral trade (Egger & Lassmann, ) or FDI (Selmier & Oh, ); recent work such as Egger and Lassmann () presents robust evidence on the direction of causality from language to trade…”
Section: Motivationmentioning
confidence: 99%
“…While our focus on the interaction between immigrants and common language skills at the country‐pair level is novel (to the best of our knowledge), we draw on several strands of literature. First, irrespective of migrant stocks, many studies have found that a common language increases bilateral trade (Egger & Lassmann, ) or FDI (Selmier & Oh, ); recent work such as Egger and Lassmann () presents robust evidence on the direction of causality from language to trade…”
Section: Motivationmentioning
confidence: 99%
“…While our focus on the interaction between immigrants and common language skills at the country-pair level is novel (to the best of our knowledge), we draw on several strands of literature. First, irrespective of migrant stocks, many studies have found that a common language increases bilateral trade (Egger and Lassmann, 2012) or FDI (Selmier and Oh, 2013); recent work such as Egger and Lassmann (2014) presents robust evidence on the 1 direction of causality from language to trade. 1 Second, Melitz and Toubal (2014) develop a global language dataset that includes not only the official language(s) of each country, but also any other language spoken by at least 4 percent of the population (such as English as a foreign language).…”
Section: Motivationmentioning
confidence: 99%